Rice seed system and its effect in rice production of Nepal - Sapkota, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
To access various types of seeds used in rice production and its effect in production a study was conducted in Kavre and Rupandehi districts of Nepal. A random sample of 50 households from Kavre district and 50 from Rupendehi districts was selected for the purpose of study. Study methods included were PRA tools, field visits including key informants’ interviews (KII), and household survey. Statistical mean, percentage, regression analysis, paired T- test were used to analyze the data. Private seed companies in Rupandehi district were found to be prominent in comparison to Kavre district. In Rupandehi district major chunk of seed was delivered through private company whereas in case of Kavre district community sector played major role to deliver seed. There was significantly high correlation (at 0.01%) between education and the use of seed. The study revealed that tendency to use improved seed was more among the educated farmers. Price of output, education level, improved seed, quantity of seed, were the explanatory variables assessed to find out their effect in rice production. The coefficient of multiple determinations (R2) of the linear return function was 0.331 indicating 33.1% of the variation in the grain yield being explained by the variables included in the equation. The F value 12.529 was highly significant. The study thus concludes that easy access of quality seed has positive impact on the rice production of Nepal. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 151-156